CLINICAL PROFILES AND OUTCOMES OF ADMISSIONS FOLLOWING COVID-19 ADMISSIONS DURING THREE WAVES OF THE PANDEMIC: EXPERIENCE OF A TERTIARY HOSPITAL IN THE EASTERN CAPE PROVINCE OF SOUTH AFRICA - KABAMBI, Freddy Kasandji; JOSEPH, Sibi Sebastian; PANICKER , Mahesh Kumar; NDLOVU, Nomagugu; EKPEBEGH , Chukwuma (African Journal of Infectious Diseases (AJID), 2024)
Background: South Africa was the country worst affected by the Covid-19 pandemic in Africa. There is a paucity of data on the clinical characteristics and mortality of Covid-19 from the Eastern Cape province of South Africa. We report on the demographic and clinical characteristics as well as the mortality of patients admitted to the Covid-19 ward of Nelson Mandela Academic Hospital (NMAH), Mthatha, during three waves of the Covid-19 pandemic in South Africa. Materials and Methods: We conducted a single centre retrospective observational study of patients admitted for Covid-19 in a tertiary hospital in the rural Eastern Cape of South Africa. Data were collected from patient files, electronic databases and the National Health Laboratory Services (NHLS) database. The outcomes were duration of admission and in-hospital mortality. Results: There were 371 patients admitted across all three waves with a mean age of 52.2 + 16.3 years. The proportion of females across the three waves is 61.2%. The commonly associated comorbidities, irrespective of the wave, were hypertension, diabetes and HIV infection. The median duration of admission was six days, with an overall mortality of 31%. The mortality for first, second and third wave were 29.3%, 31.5% and 37.9% respectively. Conclusion: Admissions for Covid-19 were predominantly in females and middle-aged. One third of the admitted patients died. Diabetes, hypertension and HIV infection were the most commonly associated comorbidities.